Enacting Relational Leadership Through Restorative Practices - Webb, Owen (Alberta Journal of Educational Research, 2021)
A restorative approach to education emphasizes that educators play a critical role in building relationships amongst school stakeholders. This case study examined the four-year journey of leading a school to implement and sustain a restorative culture. A theoretical framework for restorative practices was established around relational leadership theory and dialogue, providing the foundation for this research. The research addressed the need for studying the leading of restorative culture change from a relational perspective, while highlighting the need for leadership to establish spaces, processes, attitudes, language, and questions for establishing effective dialogue to initiate the building and sustaining of effective relations. Although the restorative culture was described by some as “diluted” by the end of the initiative, it was evident that restorative practices remained integral to the daily educational practices as a result of the four-year initiative by school leadership to integrate restorative approaches into daily practices. Key words: relational leadership, restorative practices, school culture, dialogue Une approche réparatrice de l'éducation souligne que les éducateurs jouent un rôle essentiel dans l'établissement de relations entre les parties prenantes de l'école. Cette étude de cas examine le parcours de quatre ans de la direction d'une école pour mettre en œuvre et maintenir une culture réparatrice. Un cadre théorique pour les pratiques réparatrices a été établi autour de la théorie du leadership relationnel et du dialogue, ce qui constitue le fondement de cette recherche. La recherche a répondu au besoin d'étudier la gestion du changement de la culture réparatrice d'un point de vue relationnel, tout en soulignant la nécessité pour le leadership d'établir des espaces, des processus, des attitudes, un langage et des questions pour établir un dialogue efficace afin d'initier la construction et le maintien de relations efficaces. Bien que la culture réparatrice ait été décrite par certains comme "diluée" à la fin de l'initiative, il était évident que les pratiques réparatrices restaient partie intégrante des pratiques éducatives quotidiennes suite à l'initiative de quatre ans de la direction de l'école pour intégrer les approches réparatrices dans les pratiques quotidiennes. Mots-clés : leadership relationnel, pratiques réparatrices, culture scolaire, dialogue